Complex systems and interdisciplinary research: examples of application to the phenomenon of criminality in Ecuador and Costa Rica - Muñoz Morales, R. David (2024)
Introduction. The epistemological implications of assuming Rolando García’s complex systems theory in social research are reviewed. Humanism is assumed as an affirmation that human beings are endowed with the capacity to formulate narratives about their nature, to search for an ideal of freedom and to be protagonists of their emancipation in the face of phenomena of structural violence such as that provoked by criminality in contemporary capitalism. Objective. The purpose is to reflect on how the interdisciplinary research method becomes indispensable to approach phenomena of heterogeneous elements that cannot be studied in isolation from the monodiscipline and that have the highest levels of complexity, when they are social systems. Methodology. Some examples of the application of the interdisciplinary research method to study complex systems such as the phenomenon of crime in Latin American countries experiencing recent crime booms are proposed. For this purpose, the case of crime in Ecuador and Costa Rica is chosen because they have characteristics that define them as booming systemic crises. Results. Subsystems are recognized in the scheme of criminality composed of phenomena that respond to the study of different domains of scientific knowledge but that must be approached as an organized whole in order to be understood at their respective levels of complexity. Conclusions. It is recognized that scientific progress is associated with every humanistic “outbreak” in history and that an interdisciplinary method for the study of social systems is a necessary contribution in the midst of the crises of capitalism that awaken phenomena such as modern criminality in countries once considered as an example of social cohesion.